Diverse histories, common ground and a shared future:the education of career guidance and counselling professionals in the Nordic countries - Andreassen, Inga H.; Einarsdottir, Sif; Lerkkanen, Jukka; Thomsen, Rie; Wikstrand, Frida (International Journal for Educational and Vocational Guidance, 2019)
The development of education programmes in career guidance and counseling (CGC) has followed different paths among the various Nordic countries. Ten CGC programmes in Denmark, Finland, Greenland, Iceland, Norway and Sweden were evaluated against the NICE curricular model. The results show that all NICE core competences are represented in the curricula. However, there is greater focus in some programmes on developing competences for individual career guidance, than on developing competences for working at organisational and societal levels. Implications for the cooperation and professionalisation of CGC within the Nordic countries are discussed as well as limitations of the NICE model.